Culture of Gephyrocapsa huxleyi and characterization of calcification by flow cytometry - Bourriquet Jordan; Renaudie Marie; Albrand Pierre; Cogne Guillaume; Gillon Pascale (MATEC Web of Conferences)
Coccolithophores are photosynthetic unicellular marine algae capable of producing an extracellular shell composed of calcium carbonate (CaCO3) scales called coccoliths. Photosynthesis and calcification are closely linked intracellular mechanisms and it has been proposed to use them for the development of bioconversion processes and long-term storage of CO2 in mineral form. Gephyrocapsa huxleyi (formerly named Emiliania huxleyi) is the model species of coccolithophores and the most studied. Few studies have focused on validating the methodology for monitoring these cultures. The objective of this preliminary work was to implement a culture of G. huxleyi in an artificial medium (ESAW) from a strain cultivated in natural seawater and to set up a method for monitoring cells and free coccoliths by flow cytometry. The results show that the artificial culture medium allows better growth of G. huxleyi than the natural medium, after an adaptation phase, provided that the transfer between these two environments is as progressive as possible. Flow cytometry makes it possible to count cells but must be complemented by other methods for quantitative or comparative studies. Finally, calcein seems to be an interesting marker for counting free coccoliths simultaneously with cell counting by flow cytometry.